Modeling of relay deployment in multihop relay network - Al-Dooghachi, Milad M. Ali Salih (2014)
Worldwide interoperability for microwave access (WiMAX) system is becoming more popular to be a better choice to the DSL and cable broadband services and also supports point to multi point and mesh networks. However, the fixed and mobile networks have some inherent problems such as low (SNR) at the cell edge, as well as dead spot that exists due to signal transmission is often affected by geographic conditions, such as buildings in cities and underground environments, shadowing, which leads to non lineof- sight (NLOS) communication. Therefore, WiMAX multi-hop relay technology is a key enabler to meet the growing demand and requirements for a good coverage, while minimizing the wireless backhaul requirement to increase link capacity and throughput enhancement. The MMR scheme employs relay stations (RSs) to the coverage the dead spot or can be used to provide extended network deployments temporary for emergency circumstances or special events. In this study, the performance of three hop relay network has been evaluated using the Amplify and Forward Relay (AF) and Non Amplify and Forward Relay (NAF) due to the ability of relay to provide better performance in short distance. In addition of the relay station effect on the performance of the network in different applications the three hop network in both cases was successfully evaluated to provide better link quality to subscribers and enhance the data rate of the system. In this thesis, the author proposed an accurate noise modeling for WiMAX MMR network to enhance the system performance in terms of Signal-to-Noise Ratio (SNR) estimation procedure, channel assignments, link capacity and data rate were studied based on the simulation implicated using MATLAB software version 7.4 (R2007a). The results show that the performance of system base on multi-hop relaying is one of the most promising technologies that provides a more cost-effective enhancement of coverage, user throughput (25% higher total in data rate), and provides a better link (22% higher total in link-capacity) quality to subscriptions when the RS adopts to amplify and forward (AF) scheme.